The Cost of Coastal Zone Degradation in Nigeria : Cross River, Delta and Lagos States - Croitoru, Lelia (World Bank, Washington, DC, 2020)
Nigeria is Africa’s richest economy. The country has a large population, abundant natural resources, and diverse cultures. Coastal areas are particularly unique: extending along more than 800 km, they are home to rich ecosystems, thriving industries, and booming opportunities. But these areas are also fragile. Every year, floods, erosion, and pollution of air and water have alarming consequences: they cause death, sicken children, and wash away land and houses. The poor bear the brunt. How big is the damage? This report provides a clear answer to this important question. Using a consistent valuation methodology, it estimates the cost of coastal degradation in three Nigerian states: Cross River, Delta and Lagos. The results are striking: in 2018 alone, floods, erosion and pollution in these three states cost society US$9.7 billion, or 2.4 percent of the country’s GDP. As this estimate covers less than a half of the country’s coastline, the total cost of coastal degradation in Nigeria is certainly higher. This report demonstrates the benefits of doing a coordinated study that builds on state and local level analyses. Its findings will inform the country’s multi-sectoral investment plan for the coastal zone, and will support its efforts to mobilize financing for coastal resilience as part of the West Africa Coastal Areas program. Investing in coastal resilience will save lives and prevent future damages. The time is now.